Delayed Meal Timing, a Breakfast Skipping Model, Increased Hepatic Lipid Accumulation and Adipose Tissue Weight by Disintegrating Circadian Oscillation in Rats Fed a High-Cholesterol Diet - Kim, Daeun; Hanzawa, Fumiaki; Sun, Shumin; Laurent, Thomas; Ikeda, Saiko; Umeki, Miki; Mochizuki, Satoshi; Oda, Hiroaki (Frontiers in Nutrition, 2021)
To investigate whether shifted timing of eating, breakfast skipping, induces alterations in the circadian clock and abnormal lipid metabolism, we have established a delayed meal timing (DMT) protocol for rats, which started eating food 4 h delay. In the present study, control and DMT rats were fed a high-cholesterol diet during zeitgeber time (ZT) 12-24 and ZT 16-4, respectively. The DMT protocol increased the hepatic lipids and epididymal adipose tissue weight without changes in food intake and body weight. The surge in body temperature was delayed by 4 h in the DMT group, suggesting that energy expenditure was decreased in response to DMT. The peaks of the diurnal rhythm of serum non-esterified fatty acids and insulin were delayed by 2 h and 4 h due to DMT, respectively. The oscillation peaks of hepatic de novo fatty acid synthesis gene expression was delayed by 4 h in response to DMT, whereas the peak of hepatic clock genes were 2 h delayed or not by DMT. Although metabolic oscillation is considered to be controlled by clock genes, the disintegration rhythms between the clock genes and lipid metabolism-related genes were not observed in rats fed a high-fat diet in our previous study. These data suggest that the circadian rhythm of de novo fatty acid metabolism is regulated by timing of eating, but is not directly controlled by clock genes. The present study suggests that breakfast skipping would complicate fatty liver and body fat accumulation.